1997
DOI: 10.1038/sj.cdd.4400230
|View full text |Cite
|
Sign up to set email alerts
|

Acylphosphatase is involved in differentiation of K562 cells

Abstract: The level of both isoforms of acylphosphatase was evaluated in the human erythroleukemia K562 cell line during differentiation. K562 cells were treated with PMA, which induces megakaryocytic differentiation, and with aphidicolin or hemin, which stimulate erythrocytic differentiation. While the MT isoform showed an average 10-fold increase independently of the differentiating agent used, only hemin treatment caused a similar increase of the CT isoform, suggesting a different role of the two isoforms in the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 13 publications
(15 reference statements)
0
31
0
Order By: Relevance
“…Previous studies have demonstrated that overexpression of acylphosphatase is accompanied by cell differentiation [33][34][35], and that the enzyme migrates into the nucleus during differentiation [36] as well as during apoptosis [37]. Our previous findings on the role of acylphosphatase in cell differentiation have indicated that : (i) the level of the acylphosphatase MT isoenzyme increases about 10-fold during myotube differentiation of cultured myoblasts, along with an increase in the levels of musclespecific proteins [33] ; (ii) the ectopic expression of the MT isoenzyme in K562 cells accelerates their erythrocyte differentiation [34] ; (iii) tri-iodothyronine (T $ ), a bland differentiating agent for K562 cells, activates the MT acylphosphatase gene, so that enzyme concentration is enhanced after hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that overexpression of acylphosphatase is accompanied by cell differentiation [33][34][35], and that the enzyme migrates into the nucleus during differentiation [36] as well as during apoptosis [37]. Our previous findings on the role of acylphosphatase in cell differentiation have indicated that : (i) the level of the acylphosphatase MT isoenzyme increases about 10-fold during myotube differentiation of cultured myoblasts, along with an increase in the levels of musclespecific proteins [33] ; (ii) the ectopic expression of the MT isoenzyme in K562 cells accelerates their erythrocyte differentiation [34] ; (iii) tri-iodothyronine (T $ ), a bland differentiating agent for K562 cells, activates the MT acylphosphatase gene, so that enzyme concentration is enhanced after hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3, 4, and citations therein), because it displays hydrolytic activity against the aspartyl-phosphate intermediates formed during the action of Na ϩ ,K ϩ -and Ca 2ϩ -ATPases. Other reports involve ACP in cell differentiation and apoptosis (5)(6)(7); this is because the enzyme is overexpressed when cells are induced to differentiate by certain agents, and it is able to migrate into the nucleus during both differentiation and apoptosis (8,9). The primary structure of the two isoenzymes differs in about 50% of amino acid positions, but they display very similar folds: Both consist of a five-stranded antiparallel twisted ␤-sheet flanked on one side by two antiparallel ␣-helices running parallel to the ␤-sheet (10).…”
Section: Acylphosphatase (Acp)mentioning
confidence: 99%
“…E-mail: raugei@cesitl.unifi.it Abbreviations: MT, muscle type; CT, common type; RACE, rapid amplification of cDNA ends; 3'-UTR, 3'-untranslated region; 5'-UTR, 5'-untranslated region; ORF, open reading frame; uORF, upstream open reading frame; uAUG, upstream AUG differentiation has been postulated; in fact, an increase of the MT isoform is associated with muscle differentiation [6]. Increases in both isoforms of acylphosphatase can also be observed in the K562 erythroid cell line after induction of differentiation [7]. The extent of this increase is very different between the two isoforms, depending on the differentiating agent used.…”
Section: Introductionmentioning
confidence: 99%